The Relationship Between Work Environment and Career Development on Employee Retention with Job Satisfaction as a Mediating Variable in State-Owned Enterprises in the Insurance Sector - Rhenez Alitdo Lasanov,; Intan Oktri Agtia,; Shella Yolan Anggraini,; Anita Maharani, (Jurnal Manajemen, 2023)
There is a possibility of a potential phenomenon that may occur in the next 5 years in the state-owned company in the Insurance and Pension Fund Cluster, which is the occurrence of involuntary employee turnover. This can lead to job vacancies that could be filled by Generation Z. Therefore, it is necessary to anticipate the potential departure of Generation Z in this company. This can pose a challenge to employee retention for the company. To address this, it is important to understand the factors that can influence employees to remain loyal and stay with the company. The implementation of policies in work environment, career development, and job satisfaction ultimately has a positive and significant relationship with employee retention. This study aims to determine the influence of work environment and career development on employee retention mediated by job satisfaction. Work environment and career development are exogenous variables, employee retention is the endogenous variable, and job satisfaction is the mediating variable. The results of hypothesis testing indicate that all tested hypotheses are accepted. The implementation of policies in the work environment, career development, and job satisfaction ultimately has a positive and significant relationship with employee retention.